PENGARUH PENGGUNAAN MEDIA BALOK HURUF TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN DI RA RIZKI WAHYU ANANDA KEC. PAGAR MERBAU T.A 2022-2023 - Suci Ananda; Darajat Rangkuti (Jurnal Educhild : Pendidikan dan Sosial, 2023)
The problem in this study is that children's beginning reading skills are still classified as very low, this is because teachers only use origami paper, teachers who do not use interesting learning media. The purpose of this study was to determine whether there is a significant effect of using letter block media on the ability to read the beginnings of children aged 5-6 years at RA Rizki Wahyu Ananda Kec Pagar Merbau T.A 2022-2023. The method in this study includes the type of research that uses the One-Group Pre-test-Post-test Design research design, this research is included in the type of experimental research using a quantitative approach. The results of this study concluded that there is a significant effect of using letter block media on the ability to read the beginnings of children aged 5-6 years at RA Rizki Wahyu Ananda Kec Pagar Merbau T.A 2022-2023, this is evidenced by the results of hypothesis testing using the t-test. Thitung = 2.883> 1.729, and because dk = (n-1) = (20-1) = 19 and the real level α = 0.05. Then obtained Thitung greater than Ttabel or 2.883> 1.729. Thus it can be concluded that the use of letter block media has a significant effect on the ability to read the beginnings of children aged 5-6 years at RA Rizki Wahyu Ananda Kec Pagar Merbau, this is evidenced by the results of the pre-test and post-test. It can be seen that the calculation of the average value of children before being given treatment is lower than after being given treatment. The average child's beginning reading ability after the use of letter block media is 13.85 which is in the high category, while the average value of children before the use of letter block media gets a value of 7.5 which is in the sufficient category.